The Cerebral Effect of Ammonia in Brain Aging: Blood–Brain Barrier Breakdown, Mitochondrial Dysfunction, and Neuroinflammation - Danbi Jo (Journal of Clinical Medicine, 2021)
Aging occurs along with multiple pathological problems in various organs. The aged brain, especially, shows a reduction in brain mass, neuronal cell death, energy dysregulation, and memory loss. Brain aging is influenced by altered metabolites both in the systemic blood circulation and the central nervous system (CNS). High levels of ammonia, a natural by-product produced in the body, have been reported as contributing to inflammatory responses, energy metabolism, and synaptic function, leading to memory function in CNS. Ammonia levels in the brain also increase as a consequence of the aging process, ultimately leading to neuropathological problems in the CNS. Although many researchers have demonstrated that the level of ammonia in the body alters with age and results in diverse pathological alterations, the definitive relationship between ammonia and the aged brain is not yet clear. Thus, we review the current body of evidence related to the roles of ammonia in the aged brain. On the basis of this, we hypothesize that the modulation of ammonia level in the CNS may be a critical clinical point to attenuate neuropathological alterations associated with aging.